The Development of Project-Based Science Teaching Materials in Building Collaborative Thinking and Acting Skills - Sudarmono, Joko; Rohman, Ujang; Prayogo, Prayogo (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Teaching materials are needed to improve the teaching process so that it can make learning easier. The development of project-based learning Science teaching materials aimed to to improve collaborative thinking and action skills at SMK Negeri 1 Sambeng. In this research, the researchers applied the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model reference. This model was structured programmatically with systematic activities in an effort to solve learning problems related to learning media which suit the needs and learning characteristics of students. Based on the results of the development research discussion, the results of the development of project-based science teaching in building collaborative thinking and action skills in class X Vocational Science Science subjects could be utilized and applied. It is hoped that other teaching materials with other subject matter can be developed so that it can improve teaching and learning process.